Meteorites found on Misfits Flat dry lake, Nevada. (16th March 2016) - Harlan, Scott; Jenniskens, Peter; Zolensky, Michael E.; Yin, Qing‐Zhu; Verosub, Kenneth L.; Rowland, Douglas J.; Sanborn, Matthew; Huyskens, Magdalena; Creager, Emily R.; Jull, A. J. Timothy; ,
Abstract: Meteorites have been found on the small Misfits Flat dry lakebed near Stagecoach, Nevada (119.382W, +39.348N). Since the first find on Sept. 22, 2013, a total of 58 stones of weathering stage W2/3 with a combined mass of 339 g have been collected in 19 visits to the area. This small (3.3 × 3.6 km) lakebed is now a newly designated dense collection area (DCA). Most meteorites were found in a small 350 × 180 m area along the north shore and most are fragments of several broken individual stones. Three of these fragments were classified as an LL4/5 of shock stage S2, now named Misfits Flat 001, one of which (stone MF33) fell 8.1 ± 1.3 ka ago based on the 14 C terrestrial age, assuming it came from a 20–80 cm diameter meteoroid. In addition, a small darkly crusted meteorite MF34, now named Misfits Flat 002, was found 820 m WSW from the main mass. This meteorite is classified as an LL5 ordinary chondrite with shock stage S4/5. The meteorite is saturated in 14 C at 63 dpm kg −1, suggesting it originated from the center of a 0.5 m diameter meteoroid, or deep inside a ~1.0 m meteoroid, less than 300 yr ago. Accounts exist of a fireball seen at 13:15 UT on March 2, 1895, that are consistent with the find location of Misfits Flat 002.